THE RELATIONSHIP BETWEEN SCIENCE PROCESS SKILLS AND 21ST CENTURY SKILLS IN SCIENCE LEARNING: SYSTEMATIC LITERATURE REVIEW - Azzahra, Miftahul Zannah; Nawahdani, Ahmad Mansur; Falani, Ilham (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
The purpose of this study was to explore and analyze the relationship between science process skills and 21st-century skills in science learning through the Systematic Literature Review approach. Data collection was carried out using a reference manager application, namely Publish or Perish. The search strategy used keywords developed from the main concepts, namely science process skills and 21st-century skills in science education. The collected data were then stored in *.ris format for further analysis using VOSviewer software. Bibliometric analysis was used to assess opportunities for future scientific research. This study used metadata from 400 articles. This metadata was extracted from the Scopus and Google Scholar databases. Metadata was evaluated using Vosviewer to build its visualization. This mapping process consists of three types of visualizations, namely network visualization, density visualization, and overlay visualization. The results of the study indicate that science process skills are closely related to 21st-century skills, especially in terms of critical thinking, computational thinking, and inquiry-based learning.